2011
DOI: 10.1097/iae.0b013e31821800fc
|View full text |Cite
|
Sign up to set email alerts
|

Same-Day Versus Delayed Vitrectomy With Lensectomy for the Management of Retained Lens Fragments

Abstract: The outcomes of same-day pars plana vitrectomy appear to be similar to non-same-day pars plana vitrectomy. The risks and benefits related to the timing of vitrectomy after a complicated cataract surgery should be carefully discussed with each patient. Further investigation is warranted to establish an optimal time for surgical planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The analysis estimating each study’s power for comparing outcomes was updated, and the results (mean =24%, median =14%) again indicated that many studies had low power. Figure 2A shows whether SD-PPV or DEL-PPV seemed better for each outcome, for all articles with these data 2,3,6,7,11,12,14,15,1719,22,2427,2931,34,35,40,4345. These SD-PPV vs DEL-PPV results appear mixed and do not obviously favor either vitrectomy time.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The analysis estimating each study’s power for comparing outcomes was updated, and the results (mean =24%, median =14%) again indicated that many studies had low power. Figure 2A shows whether SD-PPV or DEL-PPV seemed better for each outcome, for all articles with these data 2,3,6,7,11,12,14,15,1719,22,2427,2931,34,35,40,4345. These SD-PPV vs DEL-PPV results appear mixed and do not obviously favor either vitrectomy time.…”
Section: Resultsmentioning
confidence: 93%
“…Another statistical significance analysis, with studies separated into MCF+ (Figure 2B) and MCF− (Figure 2C), indicted that SD-PPV might have produced better outcomes in MCF+ studies2,7,11,1719,22,24,25,27,30,32,35,40,44,45 but not in MCF− studies 3,6,12,14,15,26,29,31,34,43Table 3 compares the percent of SD-PPV and DEL-PPV patients with each outcome, by MCF policy status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of vitrectomy on the development of glaucoma is unclear. While some retrospective studies found that PPV within seven days of cataract surgery was associated with a decreased risk of developing glaucoma, others reported that the development of glaucoma did not appear to be influenced by the timing of vitrectomy [14]. Others have noted a trend toward higher rates of glaucoma in the early vitrectomy group, likely due to selection bias.…”
Section: Intraocular Pressurementioning
confidence: 99%
“…15 Other studies are in agreement and did not find any relationship between the timing of vitrectomy and final visual outcome. 30,31,36,[47][48][49][50][51] However, some studies suggest that vitrectomy undertaken at the time of cataract surgery (if a vitreoretinal surgeon is available) or within 3 weeks, may improve overall visual outcome and reduce the risk for chronic elevation of intraocular pressure. [52][53][54] One systematic review and meta-analysis of retrospective interventional case series found optimal timing for vitrectomy in cases not requiring early PPV (i.e., in cases involving retinal detachment or endophthalmitis) to be between days 3 to 7 following cataract surgery.…”
Section: Timing Of Pars Plana Vitrectomymentioning
confidence: 99%